Monetary commitment and structural reforms: A dynamic panel analysis for transition economies - Ansgar Belke; Lukas Vogel (Institute for the Study of Labor (IZA), 2012)
This paper examines the contemporaneous relationship between the exchange rate regime and structural economic reforms for a sample of CEEC/CIS transition countries. We investigate empirically whether structural reforms are complements or substitutes for monetary commitment in the attempt to improve macroeconomic performance. Both EBRD and EFW data suggest a negative relationship between flexible exchange rate arrangements and external liberalization. Another finding from the EFW sample is that economic liberalisation has tended to be stronger under better macroeconomic fundamentals, suggesting that the impact of good macroeconomic conditions as facilitating structural reforms outweighs countervailing effects in the sense of lower reform pressure.
Keywords: D78; E52; E61; F36; 330; exchange rate regime; structural reform; panel data; political economy of reform; transition countries; Wechselkurssystem; Wirtschaftsreform; Wirtschaftliche Anpassung; Übergangswirtschaft; Public Choice; Transformationsstaaten